The IMMENSE Study: The Interplay Between iMMune and ENdothelial Cells in Mediating Cardiovascular Risk in Systemic Lupus Erythematosus - Bortoluzzi, Alessandra (Front Immunol, 2020)
Patients with systemic lupus erythematosus (SLE) have a significant increase in cardiovascular (CV) risk although they display a preserved number of circulating angiogenic CD3(+)CD31(+)CXCR4(+) T cells (T(ang)), a subpopulation of T cells which promotes repair of damaged endothelium. This happens due to the concomitant expansion of a T(ang) subset with immunosenescent features, such as the loss of CD28. Therefore, the aim of this study was to elucidate the interplay between T(ang) subpopulations and endothelial cells in a group of young SLE patients without previous cardiovascular events. Twenty SLE female patients and 10 healthy controls (HCs) were recruited. Flow cytometric analysis of endothelial progenitor cells (EPCs) and T(ang) subsets were performed and serum levels of interleukin (IL)-6, -8, matrix metalloproteinase (MMP)-9 and interferon (IFN)-γ were measured. Human umbilical vein endothelial cells (HUVECs) proliferation and pro-inflammatory phenotype in response to subjects’ serum stimulation were also evaluated. Results showed that the percentage of T(ang) and EPC subsets was reduced in SLE patients compared with HCs, with a marked increase of senescent CD28(null) cells among T(ang) subset. SLE disease activity index-2000 (SLEDAI-2K) was inversed related to T(ang) cells percentage. Furthermore, IL-8 serum levels were directly correlated with the percentage of T(ang) and inversely related to the CD28(null) T(ang) subsets. We indirectly evaluated the role of the T(ang) subset on the endothelium upon stimulation with serum from subjects with a low percentage of T(ang) CD3(+) cells in HUVECs. HUVECs displayed pro-inflammatory phenotype with up-regulation of mRNA for IL-6, intercellular adhesion molecule (ICAM)-1 and endothelial leukocyte adhesion molecule (ELAM)-1. Cell proliferation rate was directly related to IL-8 serum levels and EPC percentage. In highly selected young SLE patients without previous CV events, we found that the deterioration of T(ang) compartment is an early event in disease course, preceding the development of an overt cardiovascular disease and potentially mediated by SLE-specific mechanisms. The overcome of the CD28(null) subset exerts detrimental role over the T(ang) phenotype, where T(ang) could exert an anti-inflammatory effect on endothelial cells and might orchestrate via IL-8 the function of EPCs, ultimately modulating endothelial proliferation rate.